2017
DOI: 10.1177/1087054717700977
|View full text |Cite
|
Sign up to set email alerts
|

Turning Points in the Lives of Youth of With/Without ADHD: Are They Linked to Changes in Substance Use?

Abstract: ADHD individuals face challenges in making healthy decisions about SU/A due to lack of positive role models. Reinforcing accurate behavioral beliefs may be important to change behaviors in individuals with SU/A or to prevent SU/A initiation in ADHD individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Fourth, the subgroups evaluated here represented the total QIS sample (125 ADHD cases and 58 LNCG cases) described by Weisner et al (in press). However, different criteria could be applied to select subsets of the total QIS sample, as in evaluation of “turning points” by Jensen et al (in press), who selected equal subgroups of n = 20 SU Persisters, n = 20 SU Desisters, and n = 20 Abstainers for comparison, or as in the evaluation of “emotional functioning” by Mitchell et al (in press), who selected n = 67 SU Persisters and n = 25 SU Desisters for comparison. In Appendix A, the characteristics of these different subsets of the sample across the four papers of the Special Issues on the QIS are described and compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, the subgroups evaluated here represented the total QIS sample (125 ADHD cases and 58 LNCG cases) described by Weisner et al (in press). However, different criteria could be applied to select subsets of the total QIS sample, as in evaluation of “turning points” by Jensen et al (in press), who selected equal subgroups of n = 20 SU Persisters, n = 20 SU Desisters, and n = 20 Abstainers for comparison, or as in the evaluation of “emotional functioning” by Mitchell et al (in press), who selected n = 67 SU Persisters and n = 25 SU Desisters for comparison. In Appendix A, the characteristics of these different subsets of the sample across the four papers of the Special Issues on the QIS are described and compared.…”
Section: Discussionmentioning
confidence: 99%
“…The two groups were also compared on the average ratings (on a 0–8 scales, with 0 = unimportant to 8= very important) applied to the excerpts of the QIS on the 9 main topics coded for SU, and only 1 of the 7 (seeing others go “down wrong path”) showed a significant difference (ADHD = 4.99 vs LNCG = 3.85, t(72) = 2.68, p < 0.006). 2 Swanson et al (in press) described the origins of the QIS sample based on initial recruitment of ADHD (n = 576) and LNCG (n = 289) cases, retention into adulthood of the ADHD (n= 476) and LNCG (n = 267), and participation of the 4 sites of ADHD (n = 325) and LNCG (n = 159) cases. The 4 subgroups defined by Diagnosis in childhood and Persistence of substance use were compared on 5 demographic variables related to substance use (sex, and household education, social-economic, public assistance, and race/ethnicity status) with no clear evidence of confounding, and were compared on perceived frequency and reasons given in the interview for use and non-use of substances. 3 Jensen et al (in press) described additional qualitative classification procedures that yielded a total of 67 SU persisters (50 ADHD, 17 LNCG), 58 SU desisters (39 ADHD, 19 LNCG; this sample was narrowed to 33 of the 58 on the basis of heavier use [two previous assessments documenting ongoing SU] and a subsequent ≥ four years of ongoing abstinence), 32 Abstainers (18 ADHD, 14 LNCG), 16 SU Late Starters (9 ADHD, 7 LNCG), and 10 SU Resumes (9 ADHD, 1 LNCG). From these qualitative classification procedures, 10 ADHD and 10 LNCG participants were randomly selected from the SU Persister group, the SU Desister group, and the Abstainer group (male to female ratio of 4:1) to yield a final sample of 60 participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other research reported an ADHD history of close to 50% in SUD (6). The high SUD comorbidity in ADHD has been said to be related with impulsivity, social problems, less supportive families, genetic causes, and negative role modeling as well as with the adjustment of emotional dysfunction (52,53). CASS scores in girls were found to be higher than in boys.…”
Section: Table 4: Comparison Of A-des Inventory Of Parents and Peer mentioning
confidence: 97%
“…A study with adults found rates of alcohol use in persons with ADHD between 21 and 53% (54). Some persons with ADHD, even if they knew that cannabis damages cognitive and neurocognitive functions, reported to have achieved self-medication of their ADHD symptoms (52). A study published in 2017 found patients to have the impression that cannabis had a therapeutic effect on negative mood in ADHD (53).…”
Section: Table 4: Comparison Of A-des Inventory Of Parents and Peer mentioning
confidence: 99%